Molecular evidences of health benefits of drinking black tea - Rasheed, Zafar (International Journal of Health Sciences, 2019)
Drinking black tea is an excellent option if you are looking for an alternative of coffee or energy drinks. Black tea is not only a non-sweetened or less-calorie drink but also provides several health benefits as it contains powerful groups of polyphenols including epigallocatechin gallate, theaflavins, thearubigins, an amino acid L-theanine, and several other catechins or flavonoids which provide protection against the onset of several chronic disorders. Recently, Autumn Enloe has reviewed the health benefits of black tea. In her excellent review, she mentioned that drinking black tea has a range of health benefits as it contains lots of powerful antioxidants and other compounds which have potential to decrease inflammation and to reduce the risk for the onset of chronic conditions.[1] In the past two decades, research on natural health products at molecular levels has extensively performed[2-9] and their health benefits are now globally well accepted as their usage is free from side effects.[10,11] Besides water, black tea is one of our most consumed drinks obtained from a plant Camellia sinensis and now available in the markets of all over the world in both unblended form such as Assam tea, and Darjeeling tea or blended with various other plants products to obtain different flavors such as Earl Grey, Bigelow, and Chai. As we know elevated cholesterol, high triglyceride level, and obesity are directly associated with a number of cardiovascular disorders including heart attack, which are now considered as number one cause of death in all over the world.[12] Studies have shown that drinking black tea on a regular basis helps to reduce the chances of onset of cardiovascular disorders.[13,14] Gardner et al. performed databases searched from 1990 to 2004 on both aspects (helpful or harmful) of black tea, and they concluded that drinking black tea on a regular basis significantly reduced the risk of onset of heart disorders.[13] By discussing the results from some studies, they pointed out that the drinking black tea three cups per day significantly improved the antioxidant status of the body and most importantly, no credible evidence has found by them that showed back tea is harmful.[13] Moreover, similar benefits of drinking black tea on the onset of risk factors of cardiovascular disorders were reported by Bahorun et al. through their randomized controlled clinical trial.[14] Furthermore, Davies et al. also reported health benefits of black tea against cardiovascular disorders, as the inclusion of black tea in the diet reduced low-density lipoprotein cholesterol in hypercholesterolemic humans.[15] Another study also showed that drinking black tea improves the cholesterol levels not only in adults with risk of heart disorders but also in obese.[16] Besides these benefits, drinking black tea also plays a key role in reducing body weight.[17] Pan et al. reported that the polyphenols present in black tea inhibit obesity by suppressing the digestion and absorption of lipid and complex sugar. They also noticed that the black tea polyphenols also increase lipolysis and decrease lipid accumulation by reducing the proliferation of fat cells.[17] Interestingly, Pan et al. also reported that black tea polyphenols are more effective than polyphenols present in green tea.[17] Hypertension or high blood pressure is very common and is either directly or indirectly linked with several deadly complications such as heart failure, heart attack, stroke, kidney damage, and a risk of atherosclerosis.[18] Studies also show that long-term drinking black tea results in the improvement of blood pressure either from lower or higher sides.[19] Greyling et al. have reviewed and pointed out the same benefit of drinking black tea on blood pressure among normal adults.[20] In views of these findings, it is suggested that drinking black tea helps us to reduce the risk of these deadly complications associated with hypertension.[19,20] Besides these, regular drinking of black tea also reduces the risk for stroke.[21,22] Larsson et al. performed an extensively study on 74,961 stroke patients during the course of 10.2 years and concluded that drinking four or more cups of black tea on a daily basis inhibited the risk associated with stroke.[21] Not only this, Arab et al. performed a meta-analysis on black tea intake and risk of stroke. By pooling the data from nine studies on 194,965 adults including 4378 stroke patients, concluded that drinking three cups of black tea on a daily basis reduced the risk of stroke.[22] Interestingly, drinking black tea also prevents the risk of cancer onset. As Way et al. reported that black tea polyphenol theaflavins perform chemoprotective action against hormone-dependent breast tumors.[23] In addition, Liang et al. demonstrated anti‑proliferative activity of black tea polyphenol, the aflavin‑3,3-digallate on tumor cells.[24] In another study, Beltz et al. have reviewed the action of black tea polyphenols against the cancer onset and found that black tea polyphenols inhibited the survival of cancerous cells by regulating their growth and metastasis at both nucleic acid and protein levels.[25] Furthermore, Hudlikar et al. have recently reported that black tea polyphenols markedly reduced the proliferation of cancerous cells and increased their apoptosis in a dose-dependent manner in experimental animals.[26] Moreover, Singh et al. recently have given an update on molecular constituents of black tea leaves and their clinical applications. They noticed that black tea leaves contain a range of bioactive constituents including polyphenols, amino acids, volatile compounds, and alkaloids that exhibit several promising anti-disease activities at various points.[27] They mentioned that drinking black tea on a regular basis inhibited the risk of cancer onset as the phytochemicals present in black tea are known to inhibit the key events of cancer stimulation including tumor necrosis factor-α, p53, cyclooxygenase-2, nuclear factor-κB, activator protein-1, STAT, epidermal growth factor receptor, AKT, Bcl2, PARP, Bcl-xL, caspases, FOXO1, 5-LOX, and mitogen-activated protein kinases.[27] It is also important to point out that although studies at in vitro and pre-clinical levels fully supported the role of black tea against cancer development but its role at human trails level remains to be completely investigated. Beside anticancer property, consumption of black tea is also good for diabetic patients, as it is a non-sweetened drink that not only decreases the blood glucose but also reported to improve the status of insulin.[28-31] Tanga et al. reported that black tea extract reduced the blood glucose level and improved the body ability to metabolize the sugar.[29] In another study, investigators reported that black tea catechin improved the status of insulin hormone.[30] Moreover, Butacnum et al. reported that the intake of black tea improved postprandial blood sugar levels in normal and pre-diabetic adults.[31] Drinking black tea also performed the antimicrobial activity as the polyphenols present in black tea are reported to kill the growth of harmful bacteria.[32] The antimicrobial potential of black tea constituents is also proved by another study, showed significant reduction in the growth of a range of harmful bacteria.[33] Excess generation of free radicals has the ability either directly or indirectly to damage our biomolecules including the damage of nucleic acids or proteins, which has now considered being one of the key sources responsible for the induction of a number of chronic disorders.[34-40] It is now well documented that black tea polyphenols have potential to perform an antioxidant function to neutralize the harmful effects of elevated levels of free radicals, and thus drinking black tea reduced the chances of onset of numerous chronic disorders.[1,41,42] Specifically, Rietveld and Wiseman pointed out that drinking black tea 1–6 times/day significantly increased the plasma antioxidant potential in humans and decreased the oxidative biomolecular damage including the damage of nucleic acids and lipids.[41] Another mechanism was reported by Luczaj and Skrydlewska in their excellent review that black tea polyphenols inhibited the activity of pro-oxidative enzymes such as nitric oxide synthase and xanthine oxidase.[42] In short, it is now well established that drinking black tea on a regular basis improves the antioxidant potential of the body which helps us to reduce the risk of chronic disorders and to improve the overall health. However, the quality of the studies at molecular levels is still lacking to further validate the health benefits of drinking black tea. Therefore, further evidences at molecular level are required.